Enhanced Recovery after Surgery Protocol to Improve Racial and Ethnic Disparities in Postcesarean Pain Management - Felder, Laura; Cao, Connie D.; Konys, Casey; Weerasooriya, Nimali; Mercier, Rebecca; Berghella, Vincenzo; Dayaratna, Sandra (American Journal of Perinatology, 2022)
Objective The objective of this study was to assess the efficacy of an enhanced recovery after surgery (ERAS) protocol and determine its effect on racial/ethnic disparities in postcesarean pain management.Study Design We performed an institutional review board-approved retrospective cohort study of scheduled cesarean deliveries before and after ERAS implementation at a single urban academic institution. Pre-ERAS, all analgesic medications were given postoperatively on patient request. The ERAS protocol included preoperative acetaminophen and celecoxib. Postoperatively, patients received scheduled nonsteroidal anti-inflammatory drugs and acetaminophen. Oral oxycodone was available as needed, and opioid patient-controlled analgesia was eliminated from the standard order set. The primary outcome was total opioid use in the first 48 hours after cesarean, pre- and post-ERAS, reported in total milliequivalents of intravenous morphine (MME). A secondary analysis of opioid use and pain scores by racial groups was also performed. Chi-square, independent t-tests, analysis of variance, Mann–Whitney U, and Kruskal–Wallis tests were used depending on variable and data normality.Results Pre-ERAS and post-ERAS groups included 100 women each. Post-ERAS, total opioid use in 48 hours was less (40.8 vs. 8.6 MME, p < 0.001) and visual analog scale (VAS) pain scores were lower on postoperative day 1 (POD1) and 2 (POD2) (POD1 maximum at rest: 6.7 vs. 5.3, p < 0.001). Pre-ERAS pain scores differed by race with non-Hispanic Black (NHB) patients reporting the highest mean and max VAS pain scores POD1 and POD2 (POD1, maximum VAS at rest: NHB—7.4, non-Hispanic White—6.6, Hispanic—5.8, Asian—4.4, p = 0.006). Post-ERAS, there were no differences in postoperative pain scores between groups with movement on POD1 and POD2.Conclusion A standardized ERAS protocol for postcesarean pain decreases opioid use and may improve some racial disparities in postcesarean pain control.Key Points
Keywords: enhanced recovery after surgery; postoperative analgesia; racial disparities